2015
DOI: 10.1177/2331216515617917
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Binaural Pre-processing Strategies II

Abstract: Several binaural audio signal enhancement algorithms were evaluated with respect to their potential to improve speech intelligibility in noise for users of bilateral cochlear implants (CIs). 50% speech reception thresholds (SRT50) were assessed using an adaptive procedure in three distinct, realistic noise scenarios. All scenarios were highly nonstationary, complex, and included a significant amount of reverberation. Other aspects, such as the perfectly frontal target position, were idealized laboratory settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…For many listeners, different SRTs were achieved depending on which ear was attended to, suggesting a better ear for attending to speech in the presence of a masker. The phenomenon of a better ear has also been reported in a number of other studies (e.g., Baumgärtel, Hu, et al., 2015 ; Litovsky et al., 2006 ; van Hoesel & Tyler, 2003 ). There are a number of reasons why CI users have a better or preferred ear for listening.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…For many listeners, different SRTs were achieved depending on which ear was attended to, suggesting a better ear for attending to speech in the presence of a masker. The phenomenon of a better ear has also been reported in a number of other studies (e.g., Baumgärtel, Hu, et al., 2015 ; Litovsky et al., 2006 ; van Hoesel & Tyler, 2003 ). There are a number of reasons why CI users have a better or preferred ear for listening.…”
Section: Introductionsupporting
confidence: 72%
“…Depending on the time and frequencies where this occurs, the perceptual consequences on intelligibility may be situation dependent. To provide an objective measure for this algorithm, the intelligibility-weighted SNR (iSNR) ( Greenberg, Peterson, & Zurek, 1993 ) was estimated using the method described in Baumgärtel, Krawczyk-Becker, et al. (2015) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For conditions that fulfil this assumption (e.g. target speech in front and noise at one side of the listener), several studies have reported significant improvements in terms of correctly identified sentences (van Hoesel and Clark, 1995;Chung et al, 2006;Chung and Zeng, 2009) and speech reception threshold (SRT), defined as the SNR required for 50%-Carlyon & Goehring -21 st century CI 7 correct performance (Wouters and Vanden Berghe, 2001;Spriet et al, 2007;Hersbach et al, 2012;Baumgartel et al, 2015). Improvements ranged from 3.7 up to 16 dB in SRT, which can be considered as very substantial, and have been obtained using single-blinded (Chung et al, 2006;Chung and Zeng, 2009) or double-blinded designs (Spriet et al, 2007).…”
Section: Directional Microphonesmentioning
confidence: 99%
“…For users of bilateral devices, monaural SNR-enhancement algorithms are often applied separately in each device, an approach that can distort inter-aural time (ITD) and level differences (ILDs) and thus hinder the localization of sound sources (e.g., Cornelis et al, 2012; Doclo et al, 2015). The introduction of assistive listening devices that swap signals between the two ears has spawned the development of binaural pre-processing algorithms, i.e., systems that couple the functioning of two devices (Hamacher et al, 2005; Moore, 2007; Baumgärtel et al, 2015a, 2015b). One approach consists of detecting binaural cues and re-introducing them after the SNR is enhanced separately in each ear (see the review of Doclo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%